Digital Readiness and Volcanic Disaster Risk Across 55 Nations: OLS Regression and Interactive Visual Analytics - Arisaputra, Muhammad Ferrel Ganendra; Kurniawardhani, Arrie (International Journal of Informatics and Computation, 2026)
Volcanic disasters disproportionately affect countries with weak institutional capacity to use available technology. However, we have not yet tested this relationship between digital readiness and volcanic disaster risk at a global scale. This study examines whether digital readiness predicts institutional dimensions of volcanic disaster risk across 55 sovereign volcanic nations with complete data. We use the Sendai Framework for Disaster Risk Reduction 2015–2030 as the analytical structure. We integrate seven datasets, including NRI, WRI, INFORM Risk Index, GII, World Bank GDP per capita, GVP records, and EM-DAT data. We apply Pearson correlation and OLS regression to measure relationships between technology capacity and risk components. We present the results in an interactive seven-tab Streamlit dashboard. We find that NRI is strongly and negatively correlated with INFORM Risk (r = −0.781, R² = 0.609, p < 0.001). We also find a negative relationship with WRI Lack of Coping Capacities (r = −0.554, R² = 0.307, p < 0.001). We find no significant relationship between NRI and composite WRI scores driven by geological exposure. We identify Indonesia as an outlier with an above-median NRI score of 53.84. We also find a positive residual of +27.70 in coping capacity. We conclude that digital infrastructure alone does not improve disaster preparedness without governance and coordination capacity.